KELAYAKAN DAN KONTRIBUSI USAHA LEBAH MADU KELULUT DI DESA TELAGA LANGSAT KABUPATEN TANAH LAUT - Irga Hutama Ramadhan; Z. Abidin; Z. Abidin; H. Fauzi; T. Satriadi; D. Itta (Lambung Mangkurat University-Indonesia, 2021)
Tanah Laut District has been designated by the Ministry of Forestry as an area for developing Leading Non-Timber Forest Products (HHBK) in the form of honey bee cultivation. This is in line with the local government policy of Tanah Laut Regency through the Decree of the Regent of Tanah Laut Number: 188.45 / 463-KUM / 2013 which stipulates honey as the leading NTFP in Tanah Laut. The types of honey that are cultivated are bees Apis cerena, Apis mellifera and Kelulut (Trigona itama). Dusun Trans Kopi Telaga Langsat, Tanah Laut district is one of the areas where there are farmers who practice kelulut honey bee cultivation. However, so far there has been no information or study results that show how feasible the honey cultivation business is carried out by kelulut honey bee farmers in this area. This research aims were analyzed the feasibility of honey bee cultivation and its contribution to farmer household income. The data collected in this research were done by interviewing and observing. The analyzed of data had been obtained by BCR formula (Benefit Cost Ratio) to determine the feasibility of the business. The contribution of business was conducted to determine how much contribution of kelulut honey bee cultivation for farmers' household income. The results showed that the business carried out by Yamani's kelulut honey bee business had a BCR value of 5.72 with a contribution to household income of 16.77%. Meanwhile, Rudi's kelulut honey bee business has a BCR of 8.73 with a contribution to household income of 8.99%. Kelulut honey bee cultivation which is carried out by the two farmers is a type of business that is worthy of investment because the value of each BCR is more than 1 (BCR> 1).